Motivation, Communication, and Incentives for Posyandu Cadres Elderly and Performance - Setiyawan, Eltrik; Wardani, Ratna; Abiddin, Andi Hayyun (Jurnal Ilmiah Kesehatan (JIKA), 2025)
Elderly Posyandu cadres are pivotal in delivering promotive and preventive care to the older population. The efficacy of Posyandu services is intimately linked to the performance of the cadres. Various aspects that may affect the success of Posyandu cadres include motivation, communication, and rewards. This study sought to ascertain the correlation among communication motivation, incentives, and the performance of older Posyandu cadres in the Kepanjenkidul District of Blitar City. This research employed a cross-sectional study design, with 130 elderly Posyandu cadres from the Kepanjenkidul District in Blitar City as the study population. The sample approach employed a basic random sampling procedure, yielding 100 respondents who satisfied the inclusion criteria of being active cadres for over 6 months. Respondents unwilling to provide informed consent constituted the exclusion criteria. Data was gathered through a questionnaire administered in November 2023. The data analysis employed several linear regression tests. The analysis results indicated a correlation between motivation and the performance of Posyandu cadres (p-value=0,006), a correlation between communication and the performance of elderly Posyandu cadres (p-value=0,002), and a correlation between the two and the performance of elderly Posyandu cadres (p-value=0,000). Additionally, a correlation existed among motivation, communication, and incentives and the performance of older Posyandu cadres (p-value 0,000). Strategies for coaching and mentoring that Community Health Centers and Districts can be implemented to enhance the performance of older Posyandu cadres.